Can the Eastern Caribbean Currency Union Afford to Grow Old? - Monroe, Hunter (IMF Working Papers; Working Paper ;, 2009)
The demographic transition in the Eastern Caribbean Currency Union (ECCU) now underway is rapid compared with international experience, and emigration is playing a particularly large role. This paper describes and quantifies several factors which could magnify the challenge of pension reform. First, for some ECCU countries, continued emigration at historical rates would considerably advance the projected date at which pension scheme assets are depleted. Second, there is a significant risk that assets will underperform, given the large exposures to the highly-leveraged public sector and to a lesser extent the record with private sector investments. Third, portfolio diversification away from the public sector could be complicated by age-related pressure for greater central government health spending.